1990
DOI: 10.1127/nos/22/1990/7
|View full text |Cite
|
Sign up to set email alerts
|

Ammonite and dinoflagellate cyst succession of an Upper Oxfordian - Kimmeridgian black shale core from the Nordkapp Basin, southern Barents Sea

Abstract: The drilling core 7227/8-U-3 located at 72°19'05.655"N 27°33'37.635"E in the southern Barents Sea (Figs. 1 and 2) has revealed a fairly complete succession of species of the ammonite genus Amoeboceras which enables the identification of the standard Boreal ammonite zones, and some informal ammonite horizons of the Upper Oxfordian and Kimmeridgian, well established in East Greenland. The dinoflagellate cyst assemblages in the same core are dominated by seven long-ranging species. Less common are Scriniodinium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Lentin & Williams (1980) established that high relief cyst surfaces and processes are a flotation adaptation necessary in warm water (the specific gravity of water is 1.00000 at 4°C, falling to 0.99567 at 30°C). This palaeoecological trend in the Jurassic was noted by Wierzbowski & Århus (1990), Smelror (1993) and Riding & Ioannides (1996); these authors found that complex process-bearing forms are more common in the Middle-Upper Jurassic of the Tethyan Realm compared to the Boreal Realm.…”
Section: Jurassic Dinoflagellate Palaeoecologysupporting
confidence: 57%
“…Lentin & Williams (1980) established that high relief cyst surfaces and processes are a flotation adaptation necessary in warm water (the specific gravity of water is 1.00000 at 4°C, falling to 0.99567 at 30°C). This palaeoecological trend in the Jurassic was noted by Wierzbowski & Århus (1990), Smelror (1993) and Riding & Ioannides (1996); these authors found that complex process-bearing forms are more common in the Middle-Upper Jurassic of the Tethyan Realm compared to the Boreal Realm.…”
Section: Jurassic Dinoflagellate Palaeoecologysupporting
confidence: 57%
“…The Hekkingen Formation on the Barents Shelf is correlative with the Agardhfjellet Formation (late Jurassic age) on Svalbard , Nøttvedt et al 1993) and its marine fossil assemblages closely resemble those described from the Agardhfjellet Formation (Nagy and Basov 1998, Nagy et al 1988, Smelror and Below 1993, Smelror et al 2001b, Wierzbowski and Århus 1990. There are no indications of any significant biotic extinctions associated with the Mjølnir impact (Bremer et al 2001).…”
Section: Fig 1 Location Map Of the South-western Barentsmentioning
confidence: 96%
“…This is partly due to the low species diversity in the deposits, and partly to the fact that most of the recovered species are long-ranging and not particularly useful for detailed biostratigraphic subdivision of the sedimentary sequences. Endemic Boreal species are few and are, as pointed out by WIERZBOWSKI & ÄRHUS (1990), scarce in most areas, or long-ranging.…”
Section: Dinoflagellate Cyst Biostratigraphy and Biogeographymentioning
confidence: 99%
“…A well documented correlation between the Upper Jurassic ammonite zones and the dinoflagellate cyst biostratigraphy allows a more secure age-determination of the strata drilled by exploration wells. Previous studies have shown that the Upper Jurassic dinoflagellate cyst assemblages from the Barents Shelf and Svalbard (WIERZBOWSKI & ÄRHUS 1990, SMELROR et al 1998 differ significantly from those found in the Subboreal areas, and that the dinoflagellate cyst zonations defined for Britain and the North Sea (RIDING & THOMAS 1992) cannot be applied directly to the contemporaneous succession in the Boreal Province. In this respect, the present paper focused on providing new information from an "under-explored" geographic area, and a discussion of the observed differences in the characters of the Upper Oxfordian-Kimmeridgian Boreal and Subboreal dinoflagellate cyst assemblages.…”
Section: Introductionmentioning
confidence: 96%